Peran Social Capital dalam Meningkatkan Psychological Well Being Mahasiswa Pengguna WhatsApp di Universitas Buana Perjuangan Karawang - Aeni, Dwi; Rohayati, Nita; Pratomo, Yuwono (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
WhatsApp has become one of the mainstay social media of the people of Indonesia. For students, WhatsApp is very helpful in lecture activities, information about lectures, assignments, and materials can be easily accessed through  the WhatsApp application. This study aims to look at the role of social capital in  the psychological well-being of students who use WhatsApp for the benefit of lectures at Buana Perjuangan University of Karawang. Sampling using the convenience sampling  method obtained 295 samples with a population of 11,950 students. The results of the study showed that the significance value of social capital was 0.000 < 0.05 on psychological well-being, then Ha was accepted and H0 was rejected, so it can be concluded that there is an influence  of social capital on  the psychological well-being of  students who use WhatsApp for the benefit of lectures at Buana Perjuangan University of Karawang. Social capital affects the psychological well-being  of students who use WhatsApp for lectures by 35.8%. Students with  high levels of social capital tend to have  good psychological well-being, have positive relationships with others in close and wide networks, emotional support in a good social sphere, and achieve a better life.